2013
DOI: 10.1128/jcm.00100-13
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Viral Loads Lower than 50 Copies per Milliliter by Use of the Cobas AmpliPrep/Cobas TaqMan HIV-1 Test, Version 2.0, Can Predict the Likelihood of Subsequent Virological Rebound to >50 Copies per Milliliter

Abstract: b After 1 year of follow-up, patients on HAART with a baseline viral load (VL) of <20 copies/ml showed significantly lower odds of virological rebound to two consecutive VLs of >50 copies/ml than those with baseline VLs of 20 to 39 and 40 to 49 (P < 0.001). The time to virological rebound was also significantly shorter (P < 0.001) for the groups with baseline VLs of 20 to 39 and 40 to 49. T he number of patients failing antiretroviral treatment with low-level viremia (e.g., a viral load [VL] ranging from 40 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Studies that evaluated the risk of viral rebound among patients with detectable viremia below the quantification limits of conventional assays differed in their results ( Table 2). Most of the studies demonstrated an increased risk of viral rebound of Ͼ50 cpm among patients with detected viremia below the limits of conventional assays (43,48,(50)(51)(52), while two did not reveal an association (42,49). In one of the studies, Doyle et al Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Studies that evaluated the risk of viral rebound among patients with detectable viremia below the quantification limits of conventional assays differed in their results ( Table 2). Most of the studies demonstrated an increased risk of viral rebound of Ͼ50 cpm among patients with detected viremia below the limits of conventional assays (43,48,(50)(51)(52), while two did not reveal an association (42,49). In one of the studies, Doyle et al Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…In the United States, the most commonly performed virus load test is the Cobas AmpliPrep/ Cobas TaqMan HIV-1 Test v2.0 (CAP/CTM) (Roche Molecular Systems, Pleasanton, CA), a U.S. Food and Drug Administration (FDA) in vitro diagnostic (IVD) that provides high-throughput, sample-to-answer testing with real-time, reverse transcriptase PCR (RT-PCR)-based quantitation. This assay is well studied and provides a benchmark for virus load testing performance in the United States and globally (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). A recently developed test for virus load is the Aptima HIV-1 Quant Dx assay (Aptima) performed on the fully automated Panther system (both from Hologic Inc., San Diego, CA).…”
Section: Nfection With Human Immunodeficiency Virus Type 1 (Hiv-1)mentioning
confidence: 99%
“…Furthermore, even HIV-RNA levels Ͻ50 copies/ml (residual viremia [RV]) are receiving increased attention, because this level may announce beforehand a viral rebound risk in a manner that is directly proportional to the extent of the RV (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%